Penggunaan Stimulator Plus Pada Proses Fermentasi Jerami Padi Dalam Praktikum Teknologi Pengolahan Pakan - Sulistyo Sulistyo (Integrated Lab Journal, 2019)
Rice straw is a potential feed as ruminant feed. Efforts to improve its quality are essential since the high lignin content, which results in the low-quality forage. This study aimed to determine the use of “Stimulators plus” and time variation on the degradation of cellulose of fermented rice straw in feed technology practicum, to obtain the high feed quality. The materials used were rice straw, stimulator plus, starbio, urea, and molasses. Complete Randomized Design was applied with four treatments of fermentation time (0, 7, 14, and 21 days) and three replications for each treatment. The variables observed were physical and chemical quality of fermented rice straw. The results showed an increase in the physical quality of fermented rice straw (JPF) including caramel odor, easily broken texture, no fungal growth, brownish green color, and low pH value. The fermentation time at seven days improved crude protein quality, decreased neutral detergent fiber, and acid detergent fiber (P<0.01). It can be concluded that fermentation using Stimulator Plus could shorten the observation time by increasing the nutritional quality of fermented rice straw as well as other probions.